2020
DOI: 10.1186/s40479-020-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

Community-based behavioral health administrator perspectives on sustainability of Dialectical Behavior Therapy: a qualitative evaluation

Abstract: Background: Substantial resources have been invested in evidence-based practice (EBP) implementation in community settings; however, research suggests that EBPs do not always sustain over time. Method: This qualitative study explored the perspectives of 13 community behavioral health agency leaders regarding the sustainability of an EBP 25 to 28 months following the original training period. Administrators from 10 agencies were interviewed to understand the complexities of the implementation process, sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Recommendations emphasized the importance of continuous training to maintain a willing and adequately-trained workforce in the event of turnover ( Dattalo et al, 2017 ; Forman et al, 2009 ; McKay et al., 2017 ; Nelson et al, 2017 ). Suggestions included (a) a “learning period” for EBP facilitators and clinicians, which allowed them to understand that evidence-based treatments are “easy and compatible” with current practices ( Herschell et al, 2009 ); (b) online trainings as a low-cost way to keep staff trained ( Blaine et al, 2017 ); (c) increased EBP training in formal educational settings to better prepare clinicians prior to workforce entry ( Morgan et al, 2019 ; Skale et al, 2020 ); and (d) selecting clinicians who demonstrate commitment to and interest in the program or agency ( Quetsch et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations emphasized the importance of continuous training to maintain a willing and adequately-trained workforce in the event of turnover ( Dattalo et al, 2017 ; Forman et al, 2009 ; McKay et al., 2017 ; Nelson et al, 2017 ). Suggestions included (a) a “learning period” for EBP facilitators and clinicians, which allowed them to understand that evidence-based treatments are “easy and compatible” with current practices ( Herschell et al, 2009 ); (b) online trainings as a low-cost way to keep staff trained ( Blaine et al, 2017 ); (c) increased EBP training in formal educational settings to better prepare clinicians prior to workforce entry ( Morgan et al, 2019 ; Skale et al, 2020 ); and (d) selecting clinicians who demonstrate commitment to and interest in the program or agency ( Quetsch et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Workforce turnover has been measured through various organizational metrics including the number of employees leaving in a calendar year ( Aarons et al, 2009 ; Chisholm et al, 2011 ; Garner et al, 2012 ). Previous research exploring workforce turnover and EBPs has either examined associations between turnover and program implementation ( Aarons et al, 2009 ; Brabson et al, 2020 ; Woltmann et al, 2008 ), explored the predictors of turnover within EBP settings ( Brabson et al, 2019 ; Quetsch et al, 2020 ), or focused within a single discipline, like mental health services or early education ( Aarons & Sawitzky, 2006 ; Brabson et al, 2020 ; Gill et al, 2017 ; Woltmann et al, 2008 ). Recent work has begun to incorporate sustainability into the exploration of workforce turnover impact on EBPs ( McKay et al, 2018 ).…”
mentioning
confidence: 99%
“…Only few studies have investigated how outcomes of MBT are affected by changes in organization and staff ( 56 ). More studies on implementation are available for Dialectical Behavior Therapy ( 57 , 58 ) although investigators still highlight that further studies are needed to gain a better understanding of how evidence-based treatments for BPD are best implemented in real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies conducted in the US and Canada explored factors which influence sustainability as well as issues experienced by DBT teams after they completed training (Popowich et al, 2020;Quetsch et al, 2020). Broad similarities were found in both studies whereby the factors influencing sustainability were akin to those specific to implementation as reported by Swales et al (2012) and King et al (2018).…”
Section: Sustainability Of Dbt Programmes In Community Settingsmentioning
confidence: 99%
“…Two studies were based in the United Kingdom (UK: Swales et al, 2012;King et al, 2018) and reported primarily quantitative data. The other two, qualitative in nature, were based in the United States (US: Quetsch et al, 2020) and Canada (Popowich et al, 2020).…”
Section: Sustainability Of Dbt Programmes In Community Settingsmentioning
confidence: 99%